Optimizing Delivery of Breast Milk for Premature Infants: Comparison of Current Enteral Feeding Systems. (11th November 2019) - Abdelrahman, Khaled; Jarjour, Jane; Hagan, Joseph; Yang, Heeju; Sutton, Danielle; Hair, Amy
Abstract: Background: Incomplete delivery of fat from expressed breast milk (EBM) during enteral feeding to premature neonates remains a significant problem. Feeding system manufacturers have introduced changes to the enteral syringe design to improve fat delivery that have not yet been evaluated in the literature. Methods: This study compares percentage delivery of fat from EBM using 2 major enteral feeding systems in various configurations with silicone and polyurethane tubing material and ENFit and Legacy connection systems at 3 clinically relevant infusion rates. Results: The percent of fat delivery from EBM was significantly higher for the eccentric syringe system than the concentric system ( P = 0.036) but did not vary significantly across infusion rates ( P = 0.081). Silicone tubing had a significantly higher percent of fat delivery than polyurethane tubing within the eccentric syringe system ( P = 0.039) but did not vary significantly across infusion rates ( P = 0.105). There was no significant difference between ENFit and Legacy connectors using eccentric syringes with silicone tubing ( P = 0.360). Conclusion: We demonstrate that changes to syringe design and tubing material are effective and improve fat delivery from EBM, which may result in improved growth and outcomes in premature infants. The eccentric syringe marginally improves fat delivery in comparison with the concentric syringe, and silicone tubing significantly improves fat delivery compared with polyurethane tubing.